A Compact Wideband Monopole Antenna using Single Open Loop Resonator for Wireless Communication Applications - Ahmed Boutejdar; Mohammad A. Salamin; Mouloud Challal; Sudipta Das; Soumia El Hani; Saad S. Bennani; P. P Sarkar (Universitas Ahmad Dahlan, 2018)
A novel single layer, microstrip line fed compact wideband monopole antenna using open loop resonator has been designed and analyzed. The proposed antenna occupies a compact size of only 30 36.5 1.6 mm3. A partial ground plane is employed to enhance the operating bandwidth and reflection coefficient of the proposed antenna. The variations in operating bandwidth of the proposed antenna can be easily controlled by properly adjusting the position of the gap in the open loop resonator.The antenna prototype is fabricated on FR4 substrate with a dielectric constant 4.2. In this design, the antenna exhibits 10dB wide impedance bandwidth of 61% from 2.0174 to 3.7903 GHz.The antenna can be easily fed using a 50 Ω microstrip feed line and it covers the bandwidth requirements of a number of modern wireless communication systems such as IEEE 502.11b WLAN band (2.4 2.5 GHz), extended UMTS (2.5 2.69 GHz), IMT (2.7 2.9 GHz), and IEEE 802.16 Wi MAX band (3.3 3.6 GHz) applications. The desired antenna is designed and simulated using Computer Simulation Technology (CST). An extensive analysis of the antenna parameters (reflection coefficient, radiation pattern, directivity, and VSWR) including surface current distributions is presented and discussed in this paper. Good agreement between simulated and measured result is obtained.